Multimorbid Patient Experiences With Primary Care at Community Health Centers in Shanghai, China - Jin, Hua; Wang, Zhaoxin; Shi, Leiyu; Chen, Chen; Huo, Yongyan; Huang, Wuquan; Zhang, Yi; Lu, Yuan; Ge, Xuhua; Shi, Jianwei; Yu, Dehua (Frontiers in Public Health, 2021)
Objective Primary care in China is facing mounting challenges with multimorbidity as the aging population grows. Knowing how patients experience primary care may highlight the deficiencies of the care system and guide health system reform. The purpose of this study was to compare the quality of primary care experienced by patients with and without multimorbidity at community health centers (CHCs) in Shanghai, China and to examine the factors influencing these experiences. Methods A cross-sectional survey was conducted from August to December 2019 using the validated Chinese Primary Care Assessment Tool-Adult Edition (PCAT-AE). ANOVA was performed to compare the overall and domain-specific quality of primary care for patients with and without multimorbidity. Multivariate linear regressions were used to assess the factors associated with primary care quality while controlling for patients’ sociodemographic and healthcare characteristics. Results From 2,404 completed questionnaires, patients with multimorbidity reported higher PCAT scores in the domains of first contact-utilization (3.54±0.55 vs. 3.48±0.56, P<0.01), accessibility (2.93±0.49 vs. 2.86±0.47, P<0.001), and ongoing care (3.20±0.39 vs. 3.14±0.43, P<0.001), while reporting lower scores in coordination (information system) (2.72±0.41 vs. 2.79±0.35, P<0.001) and family-centeredness (3.23±0.23 vs. 3.30±0.64, P<0.01). Multimorbidity (ß=0.355, P<0.05), education level (ß=0.826, P<0.01), district (suburb: ß=1.475, P<0.001), and self-perceived good health status (ß=-0.104, P<0.001) were associated with better patient experiences in primary care. Patients between the age 61 and 70 (ß=-0.067, P<0.001; >70 years: ß=-0.076, P<0.001), with a monthly household income ≥6,000 RMB (ß=-1.385, P<0.001) and with more than 20 outpatient visits the previous year (ß=-1.883, P<0.001) reported lower total PCAT scores. Conclusion The findings of our study suggest that CHCs in China have contributed to better primary care experiences for patients with multimorbidity in certain quality domains, including first contact-utilization, accessibility, and ongoing care. However, there is still room for improvement in care coordination and family-centeredness.